Cover Image, Volume 2, Number 4, December 2020. Issue 4 (4th December 2020) - Unknown
Abstract : Front cover image : Single‐atom catalysts (SACs) with superior catalytic performance have attracted significant attention. However, because of the highly unsaturated coordination environment, the stability of SACs can be a challenge for practical applications. We review the advances and strategies for designing SACs for electrochemical applications.